SINKRONISASI KEWENANGAN PENYELENGGARAAN URUSAN DI BIDANG KEHUTANAN - Gatot Dwi Hendro Wibowo (Perspektif, 2004)
Though have taken place five year implementation the Act No. 22/1999 (improved by Act No. 32/2004), still be potential generate insist uncompromisingly or "spannungs" among central government and local, it caused by different perception in articulating authorities given by according to code. This research aim to conduct the synchronization of regulation in forestry sector In reality implementation of various authorities by Local Government still multi interpretation. Nothing uniform of legislation items among region or locally which is one with the other region. There no equality in making policy this matter is very depend on circumstance in each region or local government. The diffraction of interpretation occurred of concerning authorities among Province with the Regency or among Regency which is one with other; dissimilar in exploiting of forest resource, need the follow tai by M o U among stakeholder as existing by sense of responsibility with in management forestry resources. This M o U is expected will be express the role-sharing or role division by proportionally among stakeholder.